Assessment for the adaptation of industrial combined heat and power for chemical parks towards renewable energy integration using high-temperature TES. (November 2018) - Klasing, Freerk; Odenthal, Christian; Bauer, Thomas
Abstract: A fundamental challenge of the German energy transition is the energy supply of industrial and chemical parks based on renewable energy. Presently, the energy demand of a chemical park with one third electricity and two thirds heat as a rough estimate is commonly supplied by a heat-controlled fossil fired combined heat and power (CHP) plant. If applicable, the surplus electricity generated by such plants is sold and fed into the grid. Since the reliable energy supply of all users and facilities is priority, energy storage can be incorporated, if fluctuating renewable energy sources shall be used. This paper presents energy supply concepts without adjustments to the industrial park infrastructure or the processes themselves and proposes utilization of high temperature thermal energy storage (TES) technologies such as molten-salt, as well as power-to-heat (PtH) technology in the central CHP supply infrastructure. The objective of this study is to identify the major possibilities for integrating TES in a future energy supply system for an industrial park in Germany. It shall be shown how the flexibility of an utility supplier can be increased, so that further revenue can be generated from participating in the energy market. For this task different concepts will be proposed and applicable TES technologies will be identified. The benefits for the utility supplier and how carbon dioxide reduction and integration of renewable energies can be achieved will be highlighted. Finally, an overview of concepts with additional TES and PtH components for the energy supply of industrial or chemical parks in Germany is presented qualitatively. This overview includes the following criteria: flexibility, carbon dioxide reduction and the increased use of CHP. Overall a better understanding of potential flexibility measures for the utility supply infrastructure in the chemical industry is generated.